Analisis Pengelolaan Keuangan Diakonia Kedukaan Gereja pada Gereja Protestan di Indonesia Bagian Barat (GPIB) PNIEL Singaraja - Ginting, Beril Jurevin; Diatmika, I Putu Gede (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study aims to determine: financial management, fee system, financial reports as well as the impact and solution to the problem of late payment of church mourning diakonia at GPIB Pniel Singaraja. The type of research used in this research is qualitative. The subject of the study was the administrator and member of the GPIB Diakonia Condolences, Pniel Singaraja. Data collected by interview, observation and documentation. The results showed that: (1) the financial management of the Diakonia of Grief of the Church was managed by the manager of the Diakonia of Grief and assisted by the Congregational Council of the Church. Sources of income are in the form of entry fees and membership dues. Expenditures in the form of money and services. (2) a dues system with members paying dues. The treasurer of the church mourning diakonia hands the money to the treasurer of the church congregation, then it is deposited and deposited in a bank account. (3) supervision and audit financial reports by BPPJ GPIB Pniel Singaraja. (4) the impact of late payment of dues is a conflict between members who pay on time and members who do not pay on time, there are protests from members who pay on time to the management.